Asymptomatic malaria parasitaemia and seizure control in children with nodding syndrome; a cross-sectional study - Ogwang, Rodney; Anguzu, Ronald; Akun, Pamela; Ningwa, Albert; Kayongo, Edward; Idro, Richard (BMJ open, 2018)
Plasmodium falciparum is epileptogenic and in malaria endemic areas, is a leading cause of acute seizures. In these areas, asymptomatic infections are common but considered benign and so, are not treated. The effects of such infections on seizures in patients with epilepsy is unknown. This study examined the relationship between P. falciparum infection and seizure control in children with a unique epilepsy type, the nodding syndrome.
Keywords: Nodding syndrome; Asymptomatic malaria parasitaemia; Children